2019
DOI: 10.1371/journal.pone.0214106
|View full text |Cite
|
Sign up to set email alerts
|

Autologous adipose-derived stem cell transplantation enhances healing of wound with exposed bone in a rat model

Abstract: Objectives Soft tissue wounds with exposed bone often require extended healing times and can be associated with severe complications. We describe the ability of artificial dermis with autogenic adipose-derived stem cells (ADSCs) to promote the healing of wounds with exposed bone in a rat model. Methods Adipose tissues harvested from the bilateral inguinal regions of Wistar rats were used as ADSCs. Rats were randomly divided into control and ADSC groups to investigate th… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2020
2020
2025
2025

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 18 publications
(6 citation statements)
references
References 43 publications
0
6
0
Order By: Relevance
“…Some scientists have evidence of the benefits of using autologous stem cells to heal wounds. [13][14][15] In other studies prove the benefits of using allogeneic SC for wound healing. [16][17][18] Obviously, the use of allogeneic cells is more convenient and faster compared to the autologous material.…”
Section: Introductionmentioning
confidence: 97%
“…Some scientists have evidence of the benefits of using autologous stem cells to heal wounds. [13][14][15] In other studies prove the benefits of using allogeneic SC for wound healing. [16][17][18] Obviously, the use of allogeneic cells is more convenient and faster compared to the autologous material.…”
Section: Introductionmentioning
confidence: 97%
“…3 Adipose-derived stem cells have been shown to increase growth factors, primarily vascular endothelial growth factor and fibroblast growth factor. 4 In the present conundrum, an autologous fat graft was selected to replace the dead space of the surgical defect. The source of the fat donor site was then considered based on the closure technique to reapproximate the skin edges.…”
Section: Reconstructive Optionsmentioning
confidence: 99%
“…In addition, animal models have shown promising effects of ADSCs on accelerating wound repair. For example, treatment using artificial dermis as a supportive matrix impregnated with autogenic ADSCs in wounded rats resulted in increased vascularization and healing, which was mediated by increased gene expression of genes involved in tissue repair or angiogenesis [e.g., Tgfb-1 and -3, Fgfb and Vegf (Hamada et al, 2019)]. Also in rats, Nie et al employed an excisional wound healing model and demonstrated that ADSCs secreted pro-angiogenic mediators both in vitro and in vivo (e.g., VEGF-A, HGF, and FGF), in-turn promoting neo-vascularization and re-epithelial regeneration of wounds, thus accelerating the wound repair (Nie et al, 2011).…”
Section: Wound Healingmentioning
confidence: 99%